Primary school pre-service teachers competence level of computational concepts in programming using Dr. Scratch - Theresia Yunia Setyawan (Universitas Negeri Yogyakarta, 2020)
This descriptive research aimed at providing a general description of primary school pre-service teachers’ competence level of computational concepts in programming with Scratch using Dr. Scratch. This study analyzed Scratch projects made by 87 sophomore students of the Primary School Teacher Education Program of Sanata Dharma University as part of their Media Pembelajaran Berbasis ICT (MPBICT) course. The projects were then submitted to the Scratch Online Community platform and analyzed using a web tool called Dr. Scratch to analyze their competence level of computational concepts. The analysis results provided by Dr. Scratch showed that 75.86% of the Scratch projects belong to the category of developing projects while 22.99% of them were categorized as master projects, and only 1.15% of the projects could be labeled as basic projects. The results also revealed that the most common bad coding practices identified in the submitted projects were duplicated scripts and object namings. These results indicated that the primary school pre-service teachers of the Primary School Teacher Education Program of Sanata Dharma University had moderate competence level in integrating Scratch computational concepts such as flow control, data representation, synchronization, and user interactivity but the pre-service teachers still needed to be provided with more opportunities to work with other Scratch computational concepts such as abstraction, parallelism, and logic.